Mewujudkan Persaingan Sehat dalam Proses Pengadaan Jasa Konstruksi di Perusahaan Listrik Negara: Suatu Kajian Normatif - Lessy, Achmad Syabril; Sami’an, S.; Hardjomuljadi, Sarwono (SIGn Jurnal Hukum, 2024)
Construction services procurement at PLN Ltd carries a high risk of unfair competition practices, which can hinder the development of national electricity infrastructure. This research aims to analyze the normative framework and evaluate the effectiveness of mechanisms for preventing unfair competition practices in construction services procurement at PLN Ltd. This normative legal research employs a statute approach and a conceptual approach, with library research techniques for data collection. The research findings indicate that the normative framework governing business competition in construction services procurement at PLN Ltd is comprehensive, encompassing Law Number 5 of 1999, Law Number 2 of 2017, Presidential Regulation Number 16 of 2018, and Board of Directors Regulation Number 0018.P/DIR/2023. Nevertheless, harmonization among regulations needs to be enhanced. Implementing prevention mechanisms, such as e-purchasing and internal oversight units, is not yet optimal due to system quality, independence, and stakeholder awareness. To enhance the effectiveness of prevention, it is recommended that the implementation of GCG at PLN Ltd be strengthened, synergistic oversight by KPPU and LKPP increased, and service provider compliance with fair competition principles improved.